Facial trauma undergoing surgery: A 10-year epidemiological analysis in the interior of Brazil - Ana Júlia Maluf Coelho; Vinícius Henrique Almeida Guimarães; Nicole Ottoni Amaral; Isabela Saraiva Nemer Diório; Christian Tales Elias; Yoshio Sagata; Ari Henrique de Almeida; Marco Aurélio de Oliveira Marinho (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: Facial trauma represents significant incapacitation for the victim, as well as a challenge for healthcare teams due to its complexity and involvement of important structures. Analyzing its epidemiology allows us to coordinate public health measures to improve care and prevention. Method: Observational, descriptive, longitudinal study with a retrospective approach based on the medical records of patients who suffered facial trauma treated by the surgical clinic between 2010 and 2019. Results: Among in individuals aged 20 to 29 years, which corresponds to 31.76% of total cases. It was also more common in males, corresponding to 78.45% of total cases. Car accidents were the most common cause, described in 22.31% of medical records, and the main fracture, present in 85.83% of cases, was of the bones of the nose. Conclusion: Victims of oral and maxillofacial trauma treated at the Hospital de Clínicas da Universidade Federal do Triângulo Mineiro are predominantly men in their third decade of life, involved in automobile accidents, with injuries to the bones of the nose that were treated electively.